The main factors that have influenced students who enrolled in English Teaching Major at the Foreign Language Department of the University of El Salvador not to finish their study plan during the period 2010-2015. - García Renderos, Rebeca Noemy; Sosa Olmedo, Evelyn Cecilia; Vaquero Santamaría, Karla Vanessa (2024)
The researchers used a non-experimental study design since the purpose of non- experimental design is describing current existing characteristics such as causes, attitudes, relationships; and the main purpose of this research is to study the causes that made students who enrolled in English Teaching Major at the Foreign Language Department of the University of El Salvador not to finish their study plan during the period 2010-2015. The type of study used in this research is descriptive study. This type of study provides some aspects from the sample without changing the characteristics of the samples, which means nothing is going to be manipulated. The instrument applied helped the researchers get qualitative data to describe, explain, and validate findings. The sample responses provided information to know the factors that influenced students not finish the major in the 5 years established by the study plan 1999.